Processamento e caracterização do gel Magic-f com raios-x, espectroscopia por RMN e EPR e espectrofotometria UV/Vis - Murakami, Nayara Saty (2017)
This work aimed to perform the processing of the MAGIC-f polymeric gel, to irradiate it and to characterize it with four methods of reading, since the dosimetry with polymeric gel is a promising area within the scope of quality control of the radiotherapeutic treatments, because it allows dose evaluation three-dimensional. The methods for characterization of the MAGIC-f gel were: Computed Tomography (CT), Nuclear Resonance Magnetic (NMR) and Electron Paramagnetic Resonance (EPR) spectroscopy, and UV/Vis spectrophotometry. For characterization with this last method, a new MAGIC-f gel formulation was made adding fluorescein. The results of the characterization of this dosimetric gel with computed tomography and EPR were not satisfactory, but with NMR spectroscopy satisfactory results were obtained as well as UV / Vis spectrophotometry. The new gel formulation for characterization with UV / Vis spectrophotometry has proved to be an innovative and very promising method for this area.